2011
DOI: 10.1242/jeb.052076
|View full text |Cite
|
Sign up to set email alerts
|

Amblyomma americanum (L.) (Acari: Ixodidae) tick salivary gland serine protease inhibitor (serpin) 6 is secreted into tick saliva during tick feeding

Abstract: SUMMARYIn order to successfully feed and transmit disease agents, ticks are thought to inject serine protease inhibitors (serpins) into the host to modulate host defense responses to tick feeding, such as inflammation, the complement activation pathway and blood coagulation. In this study, we show that Amblyomma americanum (Aam) serpin (S) 6 is putatively injected into the host during tick feeding, in that the antibody to recombinant (r) AamS6 specifically reacted with the expected ~43/45kDa AamS6 protein ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 47 publications
0
53
0
Order By: Relevance
“…1B, Table 2, Supplementary Table S3). These include putative protease inhibitors such as serine protease inhibitors or serpins (Contig 1520, Contig 6586, CK178656 and Contig 688) that are similar to those described in other tick species (Anderson et al, 2008;Francischetti et al, 2010;Chalaire et al, 2011).…”
Section: Defense Mechanisms and Blood Meal Acquisitionmentioning
confidence: 94%
“…1B, Table 2, Supplementary Table S3). These include putative protease inhibitors such as serine protease inhibitors or serpins (Contig 1520, Contig 6586, CK178656 and Contig 688) that are similar to those described in other tick species (Anderson et al, 2008;Francischetti et al, 2010;Chalaire et al, 2011).…”
Section: Defense Mechanisms and Blood Meal Acquisitionmentioning
confidence: 94%
“…Antibodies used here were produced by repeated tick infestation of rabbits every 48 h (Chalaire et al, 2011) and repeatedly allowing ticks to feed to repletion (Mulenga et al, 2013). Our preliminary analysis showed that rAamAch-L non-specifically reacted with both pre-immune (PI) serum and immune sera to tick saliva proteins.…”
Section: Determining If Native Aamach-l Is Injected Into the Host Durmentioning
confidence: 98%
“…Western blotting analysis of rAamAch-L using antibodies to 48 h (Chalaire et al, 2011) and replete fed (Mulenga et al, 2013) A. americanum tick saliva proteins was carried out to investigate the possibility of native AamAch-L being injected into the host during tick feeding. The expectation is that if native AamAch-L was immunogenic and injected into the host during tick feeding, rAamAch-L would specifically bind antibodies to 48 h and/or replete fed A. americanum tick saliva proteins.…”
Section: Research Articlementioning
confidence: 99%
“…The attachment site of longistatin-silenced H. longicornis ticks did not show pathological changes, such as hemorrhagic lesions corresponding to the blood pool, while the attachment site of ticks simultaneously silenced acidic chitinases exhibited blood leakage and these ticks can be easily removed. Various protease inhibitors that have roles in anti-hemostatic, anti-inflammatory, and immunomodulatory mechanism have been also characterized using RNAi, including a cystatin, sialostatine L [81], a Kunitz type protease inhibitor, rhipilin [82], and serine protease inhibitors (serpin) [83,84].…”
Section: Genes Related To Salivary Functionsmentioning
confidence: 99%